Does Anti-dumping Enforcement Generate Threat?. (February 2014) - Bagchi, Sagnik; Bhattacharyya, Surajit; Narayanan, K.
The last two decades have witnessed that countries across the world are guided by the rules and regulations of multilateral trading institutions (for example, World Trade Organization [WTO], International Monetary Fund [IMF]) in order to promote free and fair trade through gradual reduction in trade barriers. The world economy has noticed significant reduction in tariffs, yet we find a rise in non-tariff barriers (NTBs). However, we still find dumping and few other trade strategies of the exporting countries as a major hindrance to free and fair trade. Such behaviour has led to 'contingent protection' as a tool of new-protectionism . Among the contingent protection measures, anti-dumping (AD) has evolved as the most popular choice of strategy for the trading nations. The AD policy invokes a threat to the exporter and thereby can change its strategic behaviour. We describe the phenomenon of dumping through a price-leadership model and thereby compute the optimal level of AD duty that can offset dumping. Using a sequential game, we conclude that the credible threat of an AD duty restricts dumping and thereby leads to a win-win situation for both the foreign and domestic firms.